The Importance of Qualitative Addition to the New Arbitration Rules in the Settlement of International Disputes Study of the Experience of the Kingdom of Bahrain International (Global Journal of Human-Social Science, 2023)
The UNCITRAL Arbitration Rules have added a comprehensive set of procedural rules on which parties can agree to apply arbitration procedures that may arise out of their commercial relationship and which are widely used in ad hoc arbitrations as well as in arbitrations administered by institutions The rules cover all aspects of the arbitration process as they include a model arbitration clause set out rules of procedure for the appointment of arbitrators and the conduct of the arbitration proceedings and establish rules regarding the form effect and interpretation of the arbitral award Currently there are three different versions of the arbitration rules i the 1976 version ii the 2010 revised version and iii the 2013 version which was a qualitative addition to the Rules of International Arbitration Dispute Resolution where Bahrain benefited from this addition in the development of the rules previously in force
Keywords: arbitration rules - modern - dispute settlement - kingdom of bahrain